Evaluation of radial voidage profiles in packed beds of low-aspect ratios - Mariani, Nestor Javier (2000)
The relationship between the radial voidage profile, ϵ(r), and the radial distribution of centres of mono‐sized spherical particles, f(r), is revised. A close expression is given for the section S(r1, rc), the area of the segment of a cylindrical surface of radius r intersected by a particle centred at rC. From this expression, ϵ(r) can be evaluated straightforwardly from the knowledge of f(r). The range 1≥ a ≥ 2 of aspect ratios (a = dT/dp is then analysed specifically. For this range, the distribution of spherical particles has been characterized theoretically (Govindarao et al., 1992) and a simple expression allows the evaluation of ϵ(r). The use of this expression for actual catalyst particles, imperfect spheres showing a distribution of sizes, in finally analyzed.